"Cancelled Dreams": Family Reunification and Shifting Canadian Immigration Policy. Issue 1 (2nd January 2016) - Bragg, Bronwyn; Wong, Lloyd L.
ABSTRACT: Drawing on a collection of personal interviews with immigrant families, this article documents the impact of recently introduced restrictive family reunification policies on immigrants living in Canada today. Since 2008, Canadian immigration policy has changed dramatically with renewed neoliberal emphasis on economic immigrants and labor-market integration. This article explores the impact of this policy shift on immigrant families and on immigrant women and children in particular. This article argues that there are profound human costs to limiting family reunification; these costs are disproportionately borne by immigrant women and ultimately impact immigrant integration and belonging.